Characterization of a Sulfhydryl Oxidase From Plasmodium berghei as a Target for Blocking Parasite Transmission - Zheng, Wenqi; Liu, Fei; Du, Feng; Yang, Fan; Kou, Xu; He, Yiwen; Feng, Hui; Fan, Qi; Luo, Enjie; Min, Hui; Miao, Jun; Cui, Liwang; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Quiescin sulfhydryl oxidase (QSOX), present in a wide variety of eukaryotic species, catalyzes the insertion of disulfide bonds into unfolded, reduced proteins. Here we characterized the QSOX protein from the rodent malaria parasite Plasmodium berghei (PbQSOX), which is conserved in all sequenced malaria parasite species. The PbQSOX protein was not expressed in asexual erythrocytic stages, but was most abundantly expressed in ookinetes. Indirect immunofluorescence assays revealed PbQSOX was not only localized in cytoplasm of gametocytes, gametes and ookinetes, but also expressed on the surface of gametes and ookinetes. Western blot identified extracellular presence of PbQSOX in the culture medium of ookinetes suggestive of secretion. Pbqsox deletion (Δpbqsox) did not affect asexual intraerythrocytic development, but reduced exflagellation of male gametocytes as well as formation and maturation of ookinetes. Pbqsox deletion also led to a significant increase in the reduced thiol groups of ookinete surface proteins, suggesting that it may play a role in maintaining the integrity of disulfide bonds of surface proteins, which might be needed for ookinete development. Mosquitoes that fed on Δpbqsox-infected mice showed a significant reduction in ookinete and oocyst numbers compared to those fed on wild-type parasite-infected mice. Further, both polyclonal mouse antisera and a monoclonal antibody against the recombinant PbQSOX exhibited substantial transmission-blocking activities in in vitro and mosquito feeding assays, suggesting QSOX is a potential target for blocking parasite transmission.